The Use of Target Cost Technique To Achieve Competitive Advantage Applied Study In The General Company For The Car Manufacturing And Equipment - Mechanical Plant - Alaa Abdul Hassan Hassan Al– Mohammadi; Salma Mansour Saad al-Rubaie (Journal of Madenat Alelem University College, 2020)
The product of the Iraqi industrial companies face sharp competition in the market for several reasons, the most important of which is its high cost compared to foreign products, as well as weak government support for national products, which led to its decline and its inability to compete. Therefore, the research aims to demonstrate the knowledge bases of target cost technique and competitive advantage, The main objective of the research is that the work of target cost technique helps to reduce costs, Ware current product in according to the requirements of customers, which helps the economic unit in achieving a competitive advantage to compete and survive in the market.